Lithium-discontinuation-induced treatment refractoriness revisited - Ralph Kupka; Eline Regeer; Annet van Bergen; Leonardo Tondo; Michael Bauer (International Journal of Bipolar Disorders, 2024)
Abstract Background Lithium is effective in the long-term treatment of bipolar disorder. Concerns have been raised about non-responsiveness after discontinuation and resuming previously effective lithium prophylaxis. We reviewed the available literature on this so-called lithium-discontinuation-induced treatment refractoriness (LDITR). Results We found 11 case reports and six cohort studies including 403 patients addressing LDITR, and one nation-wide register study providing some additional data on LDITR. Pooling all cohort studies, the percentages of non-responders during re-treatment with lithium ranged from 3.6 to 27.7%, with an average of 17.3%. Non-responsiveness was associated with longer duration of lithium treatment before discontinuation, longer duration of bipolar disorder before start of lithium, faster tapering off lithium, and longer duration of discontinuation. Conclusions There may be a subgroup in whom lithium discontinuation-induced treatment refractoriness exists. However, the vast majority of people respond when lithium is restarted. Moreover, it may be necessary to continue lithium beyond the first relapses to restore long-term prophylactic efficacy.